A 3-min all-out upper-body ergometer test for competitive swimmers - Baastrup Nordsborg, N.; Aragón-Vela, J.; Bonne, T.; Mohr, M. (International Journal of Sports Medicine, 2021)
We examined the application of a land-based swimming ergometer 3-min all-out test to determine physiological predictors of swimming performance. Fourteen young elite swimmers participated (males: n=6; females: n=8). The swimmers completed two 3-min upper-body all-out tests on a swimming ergometer. Additionally, the swimmers completed freestyle swim races ranging from 50 m to 1500 m. High test-retest reproducibility (r=0.98 and coefficient of variation values <7.5%) was evident for ergometer derived peak, mean and critical power. Very strong correlations (r>0.87, p<0.001) were obtained between the 200-, 400-, 800- and 1500-m swimming performances and derived critical speed. Moreover, correlations were found between peak force and peak power and 50-m performance, in addition to critical power and performance for all distances. The critical speed was the dominant predictor of 200- to 1500-m performances (r=0.84-0.99). In conclusion, the land-based 3-min all-out swimming ergometer test is reliable and valid in predicting swimming performance in competitive swimmers and evaluates important physiological components in swimmers independent of technical abilities.